EFEK PEMBERIAN MASSAGE BAYI DAPAT MENINGKATKAN KUALITAS TIDUR BAYI NORMAL USIA 0 – 6 BULAN DI POSYANDU PERMATA HATI - Siti Muawanah; Futhri Rifa Zaimsyah; Nova Relida (LPPM Universitas Abdurrab, 2019)
Sleep is one of the needs of a baby or child that is as important as other primary needs. One way to fulfill your baby's sleep needs is by massage. Touch on the skin will stimulate blood circulation and will increase the oxygen wave energy that is more sent to the brain so that the circulation system and respiration spur better. Feeling comfortable and relaxed due to massage will improve sleep quality. In addition, it can increase the production of Asi, increase body weight, increase endurance, in infants 0-6 months. The purpose of this study is to prove that massage can improve the quality of sleep for babies 0-6 months. The method of dedication was carried out by tearing the hearts of the 13 people in one group and were intervened with infant massage. in normal infants 0-6 months. The conclusion of this service is that there is the effect of giving a baby massage to the sleep quality of a normal baby 0-6 months